Urinary Excretion of C5b-9 is Associated With the Anti-Angiogenic State in Severe Preeclampsia - Guseh, Stephanie H.; Feinberg, Bruce B.; Dawood, Hassan Y.; Yamamoto, Hidemi S.; Fichorova, Raina N.; Burwick, Richard M. (American journal of reproductive immunology (1989), 2015)
Problem Severe preeclampsia has been independently linked to complement dysregulation and angiogenic imbalance; however, the relationship between complement and angiogenic factors in human pregnancy is unclear. Method of study Utilizing existing biomarkers, our study sought to better understand this relationship in active disease. We performed a case–control study, enrolling 25 cases with severe preeclampsia, 25 controls with chronic hypertension, and 25 healthy controls without hypertension. Levels of complement components (C3a, C5a, and C5b‐9) and angiogenic markers [basic fibroblast growth factor (bFGF), placental growth factor (PlGF), vascular endothelial growth factor (VEGF), and soluble fms‐like tyrosine kinase‐1 (sFlt‐1)] were measured simultaneously. Results Compared to both hypertensive and non‐hypertensive controls, severe preeclampsia was associated with increased plasma sFlt‐1, decreased plasma VEGF and PlGF, decreased urinary PlGF, and increased urinary C5b‐9. Urinary marker C5b‐9 correlated strongly with the anti‐angiogenic condition. In subjects with detectable urinary excretion of C5b‐9, median plasma levels of sFlt‐1 were significantly greater (32,029 versus 4556 pg/mL, P < 0.0001) and levels of PlGF (15.6 versus 226 pg/mL, P < 0.0001) and VEGF (119 versus 153 pg/mL, P = 0.001) were significantly lower. Conclusion More so than plasma complement markers, urinary C5b‐9 may a useful measure to link complement dysregulation with angiogenic imbalance in severe preeclampsia.